Evaluasi Kinerja Pengasuh Dalam Pembimbingan, Pengawasan Dan Pembinaan Disiplin Praja di Bagian Pengasuhan Kampus IPDN Jatinangor - Sedarmayanti, Sedarmayanti; Amalia, Rizki (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2013)
This research aims to evaluate the performance of the caregiver in mentoring, supervision, and coaching disciplines of Praja in nurture section of IPDN Jatinangor campus. This research used a qualitative descriptive approach method. This research evaluated the performance of the caregiver with aspects studied were competelices (which includes: knowledge, understanding, skills and experience), attitudes and actions. In addition, this research is also to determine the factors that affect the performaiwe of the caregiver and the obstacles, while the aspects studied were caregiver competence, structure and coordination. The results showed that the performance of the caregiver in mentoring, supervision, and coaching disciplines of Praia in nurture section of IPDN Jatinangor campus needs to be improved or optimized in terms of competences, attitudes and actions. Later it was found that there are .factors that affect the performance of the caregiver and also obstacles namely caregiver's competences, organizational structure of nurture section and coordination of caregivers, while the efforts to overcome the obstacles of caregiver performance were caregiver competence increased, improvement of the structure of Nurture Section, and caregivers coordination increased.